Convenient synthesis of the enantiomerically pure (S)-2,4-dihydroxybutyl-4-hydroxybenzoate using hydrolytic kinetic resolution - More, N. A.; Jadhao, N. L.; Garud, D. R.; Gajbhiye, J. M. (Synthetic Communications, 2018)
(S)-2,4-Dihydroxybutyl-4-hydroxybenzoate was prepared in an extremely simple and practical way with high enantiomeric excess (99% ee) using Jacobsen’s Hydrolytic Kinetic Resolution technique as a key step and source of chirality.